Visceral hypersensitivity in endometriosis: a new target for treatment?. Issue 3 (25th August 2011) - Issa, B; Onon, T S; Agrawal, A; Shekhar, C; Morris, J; Hamdy, S; Whorwell, P J
Abstract : Objective: In women presenting to gynaecological clinics with lower abdominal pain, the cause is frequently attributed to endometriosis irrespective of whether it is found to be minimal or extensive at laparoscopy. Irritable bowel syndrome (IBS) is also common in this setting, and it was speculated that the visceral hypersensitivity associated with this condition might be amplifying the symptoms of endometriosis. Methods: Visceral sensitivity to balloon distension, symptoms and psychological status were assessed following laparoscopy in 20 women with minimal to mild endometriosis, 20 with moderate to severe endometriosis, 20 with laparoscopy negative abdominal pain and 20 asymptomatic women undergoing laparoscopic sterilisation who acted as controls, and compared with 20 women with IBS. Results: Compared with controls, patients with minimal to mild and moderate to severe endometriosis had a higher prevalence of symptoms consistent with IBS (0% vs 65% and 50%, respectively, p<0.001) with significantly lower mean pain thresholds (39.5 mm Hg (95% CI 36.0 to 43.0) vs 28.1 mm Hg (95% CI 24.5 to 31.6), p=0.001 and 28.8 mm Hg (95% CI 24.9 to 32.6), p=0.002) not explained by differences in rectal compliance. Patients with laparoscopy negative pain had symptoms and visceral sensitivity similar to patients with IBS. Controls undergoing laparoscopy had normal sensitivity, indicating that the laparoscopic procedure was not inducing hypersensitivity. Conclusion: Visceral hypersensitivity is extremely common in endometriosis and could be intensifying the pain. This finding might explain why mildly affected individuals often complain of severe symptoms out of proportion to the extent of their disease. This study has introduced a completely new concept into the understanding of pain in endometriosis and could open up new opportunities for treatment.